Social value appraisal: cutting the Gordian knot - Irene D.M Ciccarino; Susana Cristina Serrano Fernandes Rodrigues; Jorge Ferreira Da Silva (Innovation & Management Review)
Purpose – Social initiatives must disclose their results to access support. However, there is no theoretical consensus about how to do it. It is still necessary to understand the value creation in social initiatives because they may or not have economic goals. However, these goals serve to make the social ones feasible. This study aims to cut this Gordian knot by providing measures aligned to the value theory but developed by the social lens. It offers a non-economic-focused approach to dealing with assessment complexity and with multiple stakeholders’ needs for information. Design/methodology/approach – A consolidation research path is suggested by three composed measures built upon tested and reliable scales. These value measures are discussed through narratives from Portuguese investors and social entrepreneurs in a mixed-methods design. Content analysis and online survey provided data for descriptive statistics, exploratory factor analysis and Cronbach's alpha test. Findings – The analyses supported the value measures. Thus, they allow an effective way to assess and report the social value created. It also highlighted a potential use in preventive and corrective approaches helpful for several organizations that pursue social goals. Research limitations/implications – The measures were tested based on social entrepreneurs' opinions. Future studies can include beneficiaries' opinions, allowing comparisons that can help to set more realistic goals and better investment criteria. Originality/value – The relationship between investors and initiatives can improve, boosting their impact on society. The measures can highlight prioritization choices that influence the way value is created. Hence, they serve as a sensemaking from a holistic standpoint.